2019
DOI: 10.1111/hepr.13356
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of chemokine C‐C receptor 7/programmed cell death‐1+ follicular helper T cell subset frequencies in the diagnosis of autoimmune hepatitis

Abstract: Aim A significant concern for autoimmune hepatitis (AIH) patients is diagnostic specificity. Delayed treatment due to delayed diagnosis leads to poor survival. We recently reported that chemokine C‐C receptor 7 (CCR7)−/programmed cell death‐1 (PD‐1)+ follicular helper T (Tfh) cells could be involved in AIH pathogenesis. We hypothesized that Tfh cell frequencies might contribute to AIH diagnosis. Methods Peripheral blood was collected from 12 patients with AIH from April 2013 to March 2016, as well as 24 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…detected levels of CCR7 – PD‐1 + TFH cells in autoimmune hepatitis and HBV‐infected patients, and found that the frequency of CCR7 – PD‐1 + TFH cells increased significantly in autoimmune hepatitis patients compared with that in healthy controls. However, the level in HBV‐infected patients did not change significantly, and this result is consistent with the present results . The differential expression of TFR and TFH in the peripheral blood of CHB patients suggests that B cell‐associated immunity in CHB patients may be inhibited compared with healthy controls, and antibody production and function may be affected.…”
Section: Discussionsupporting
confidence: 91%
“…detected levels of CCR7 – PD‐1 + TFH cells in autoimmune hepatitis and HBV‐infected patients, and found that the frequency of CCR7 – PD‐1 + TFH cells increased significantly in autoimmune hepatitis patients compared with that in healthy controls. However, the level in HBV‐infected patients did not change significantly, and this result is consistent with the present results . The differential expression of TFR and TFH in the peripheral blood of CHB patients suggests that B cell‐associated immunity in CHB patients may be inhibited compared with healthy controls, and antibody production and function may be affected.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the authors identified CCR6 + Tfh cells and revealed the importance of the CCR6-CCL20 axis in the migration of CCR6 + Tfh cells to the liver. 219 Kimura et al 220 , 221 found that the level of CCR7 − Tfh cells was elevated in PBMCs of AIH patients with low levels of IgG, which may be helpful for early diagnosis of AIH. Ma et al 222 found that Lactobacillus enhanced the therapeutic effect of prednisone in both AIH patients and experimental AIH mice.…”
Section: Differentiation Of Cd4 + T-cell Subsetsmentioning
confidence: 99%
“…Thus, the function of MZP B cells in supporting the migration of Tfh cells through CCR7 needs further confirmation. Notably, cTfh cells with low CCR7 expression are increased and have been described as an indicator in autoimmune diseases including AIH ( 148 ) and pSS ( 125 ), as well as chronic HBV infection ( 149 ). CCR7 int Tfh cells in the blood are closest to tonsillar Tfh lineage cells and exhibit a more potent capacity to induce memory B cells to differentiate into antibody-producing cells than CCR7 high Tfh cells ( 150 ).…”
Section: Novel Insights Into Breg-mediated Regulation Of Tfh and Tfr In Autoantibody Productionmentioning
confidence: 99%